2020
DOI: 10.1108/jkm-01-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

A structured MPA approach to explore technological core competence, knowledge flow, and technology development through social network patentometrics

Abstract: Purpose This study aims to propose a methodology by integrating three approaches, namely, internal core technology, external knowledge flow and industrial technology development to help companies improve their decision-making quality for technology planning and enhance their research and development (R&D) portfolio efficiency. Design/methodology/approach The primary focus of this study is thin-film solar technology and patent data is retrieved from the United States Patent and Trademark Office (USPTO) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…In fact, according to Giglio, (2021), prior innovations always provide some quotas of relevant knowledge, which (directly or indirectly) contribute to either the "learningby-acquisition" process or the creative one. This is coherent with Lai et al, (2021) findings on knowledge flows and patent connectivity, that may form a technology development path over time (see also Hummon and Dereian, (1989). In detail, when prior acquired knowledge is not utilized -i.e.…”
Section: Variables and Measuressupporting
confidence: 83%
“…In fact, according to Giglio, (2021), prior innovations always provide some quotas of relevant knowledge, which (directly or indirectly) contribute to either the "learningby-acquisition" process or the creative one. This is coherent with Lai et al, (2021) findings on knowledge flows and patent connectivity, that may form a technology development path over time (see also Hummon and Dereian, (1989). In detail, when prior acquired knowledge is not utilized -i.e.…”
Section: Variables and Measuressupporting
confidence: 83%
“…2, there is only one path between any pair of nodes. For calculation we need to consider all pairs of nodes from {2,3,4,5} , which is 6 {(2,3), (2,4), (2,5), (3,4), (3,5), (4, 5)}. Furthermore, only one path exists between each pair that passes through node 1.…”
Section: ) Eigenvector Centralitymentioning
confidence: 99%
“…Patent data can be analyzed to identify multiple dimensions of an innovation landscape. Using patent analysis, previous studies have identified trends and trajectories of evolving and established technologies [3][4], technology convergence and divergence, and firm innovation capabilities. Patent citation analysis is employed to assess the knowledge flow [5][6], as well as knowledge providers and absorbers [7] across the technology trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…First, this paper contributes to extending prior research investigating the consequences of knowledge flow by exploring the relationship between relational risks and knowledge flow. Previous studies indicate that the preconditions required for knowledge flow are mainly frslom network resource (Huggins and Johnston, 2010), inter-firms patterns (Melissa, 1996) and technological core competence (Lai et al , 2020). Moreover, combined with the knowledge-based view and network theory, relational risks regard, as an internal factor, knowledge flow within the process of R&D projects (Delerue and Simon, 2009; Tang, 2006).…”
Section: Implications and Limitationsmentioning
confidence: 99%